Ethics of Qur’anic Communication in the Era of Artificial Intelligence: Perspectives from Ibn ʿAshur’s Tafsir - binti Abd Kadir, Kauthar; Hoque, Mesbahul; Rafindadi, Uwaisu Babba (Suhuf: International Journal of Islamic Studies, 2026)
Background: Rapid AI growth and digital communication have intensified concerns regarding misinformation, algorithmic bias, and manipulation. Islamic ethical thought provides enduring principles to address these modern socio-technical challenges. Objective: This study examines Qur’anic communication ethics through Muhammad al-Tahir Ibn ‘Ashur’s Tafsir al-Tahrir wa al-Tanwir. It aims to develop a comprehensive, value-based framework that bridges classical exegesis with AI-mediated contexts, providing a moral foundation for digital governance and addressing systemic ethical gaps in automated systems. Methodology: Using a qualitative design, the study analyzed Qur’anic verses on speech and interaction through Ibn ‘Ashur’s lens. Thematic analysis was employed to identify and synthesize recurring ethical values and principles. Results: Five core values emerged: truthfulness (sidq), wisdom (hikmah), gentleness (lin), justice (adl), and public interest (maslahah). This maqasid-oriented framework links moral guidance with social welfare, suggesting these principles can effectively mitigate AI risks such as bias, deception, and exploitative digital practices. Conclusion: Ibn ‘Ashur’s interpretation provides a robust Qur’anic ethical model highly relevant to contemporary communication and technological challenges.